Confirmation of male well-being indicators in Malaysia - Siti Zaiton Mohd Ajis,; Arina Anis Azlan,; Emma Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Assessing well-being can be tricky due to its subjective nature which may result in inaccurate or incomplete evaluations. This is particularly challenging in measuring male well-being, as traditional gender roles and expectations often discourage normalizing discussions about men’s health concerns. Studies reveal notable obstacles in the way men perceive, behave, and hold beliefs about their health and well-being which may result in underreporting of health issues among men. A gender-specific measurement of well-being for men is therefore essential and merits further examination. This study aims to validate a male well-being instrument in the context of Malaysian men using confirmatory factor analysis (CFA). An online cross-sectional survey involving a total of 651 Malaysian men aged 18 and above was conducted utilizing a 33-item male well-being instrument developed in a preliminary study. The analysis resulted in a satisfactory 24-item model with six dimensions of self-confidence, family/close relationships adaptation, physical health, living environment adaptation, autonomy and agency, and economic stability. There were high correlations among the 24 items. The internal consistency reliability was robust, with no floor or ceiling effects. These results represented equivalence and consistency among the responses to items, suggesting that the items were homogenous in measuring Malaysian male well-being. This study confirms the suitability of a 24-item instrument measuring male well-being in Malaysia. The instrument may possibly be used in similar Asian cultures as it achieved strong reliability, structural validity and construct validity that fulfilled goodness-of-fit criteria.